Organizational Behavior, Global Edition - Robbins, Stephen P.; Judge, Timothy A.; Robbins, Stephen (Pearson International Content, 2023)
Organizational Behavior provides the information you want, when you want it. Reflecting the most recent research and events within the field of OB, the 19th Edition continues its hallmark focus on clear writing, cutting-edge content, and intuitive pedagogy. There's a reason why Robbins's textbooks have educated millions of students and have been translated into 20 languages: because of a commitment to provide engaging, cutting-edge material that helps you understand and connect with this important field of study.